A cloud computing-based framework for internationalisation of SMEs. (1st January 2013) - Sharma, Durgesh; Garg, Suresh K.; Sharma, Chitra
The paper examines the current growth rate of the Indian auto component industry and its contribution to the global markets. Recent researches have concluded that low and ineffective adoption of IT by the manufacturers is one of the primary reasons of the dismal contribution of the sector to the export markets. Majority of the firms operating in this sector are small and medium enterprises (SMEs) who cannot afford to invest in world class IT solutions. The diversity and tiered structure of the industry further complicates the process of adoption of IT practices. The paper presents a community cloud-based framework for crafting the IT strategy and further accelerating the adoption of IT among the Indian auto manufacturers. It also shows how the framework can be used for achieving effective supply chain integration in the sector.